Air Quality Analysis in the Service Room Siti Fatimah Mother and Child RSKD, South Sulawesi Province - Putri Amalia Andini (Manunggal Halim Jaya, 2021)
Water as an environmental component that is important in life needs to be maintained and enhanced. Indoor air quality is not only affected by chemical pollution but also by physical environmental factors such as temperature and humidity. Based on the data obtained in the area of the building in the Siti Fatimah Hospital of Mother and Child the building area of 1.808 m2 consists of IRD is 15 x 19 m2, the delivery room is 11 x 27 m2, perinatology 10 x 15 m2, operating room is 14 x 21 m 2 the treatment room class I 7 x 11 m2 and classrooms II 10 x 18 m2. The delivery room can be occupied by only eight patients and five officers and the IRD patient room max 4 people with five officers. But every room of the patients who were hospitalized brought a companion of more than two people, causing a buildup in the room caused the release of CO2 over the limit of the maximum access door of the room service provided 3 but there is only one access door located in the delivery room that used the place out which led to the end uncontrolled. Methods: The purpose of this study is to analyze the quality of air in the room service (IRD, delivery room, operating room, and NICU) and treatment room (class 1 and class 2) at Siti Fatimah Hospital of Mother and Child. This type of research is observational research, whereas the research design used Cross Sectional methods by analyzing air quality through the presence of germs in the air by connecting the parameters of the physical environment (temperature, humidity, lighting, and dust in space), and the population density in the room service and the treatment room Hospital of Mother and Child Siti Fatimah South Sulawesi province. The analysis was performed with the chi-square test and correlation matrix Results: The results showed there is a lighting effect on the existence of germs with a p-value of 0.032 (P <0.05) with value of correlation r = 0.410, which means the power to do a moderate but still there is a relationship. Suggestion: Preferably in-room service and care at the Hospital of Mother and Child Siti Fatimah no kitchen to prevent the increase of CO2 before the bacteria thrive and are contaminated by the patient's health officials, and the public who were around the area of the hospital.